Molecular mechanisms of the metabolite 4-hydroxytamoxifen of the anticancer drug tamoxifen: use of a model microorganism - Monteiro, J. P. (2003)
A strain of the thermophilic eubacterium Bacillus stearothermophilus was used as a model system to identify membrane mediated cytotoxic effects of 4-hydroxytamoxifen, following previous studies with tamoxifen. With this experimental approach we attempted to further clarify tamoxifen and 4-hydroxytamoxifen membrane interactions often evoked as responsible for their multiple cellular effects. Bacterial growth and the oxygen consumption rate provided quantitative data of the cytotoxic action of hydroxytamoxifen. The effects of hydroxytamoxifen on the physical properties of bacterial lipid membrane preparations were also evaluated by fluorescence polarization of 1,6-diphenyl-1,3,5-hexatriene. Cultures of B. stearothermophilus grown in a complex medium containing hydroxytamoxifen in the concentration range of 1 to 7 [mu] exhibited progressively longer lag adapting periods, decreased specific growth rates and lower growth yields, as compared to control cultures. Hydroxytamoxifen also affected the electron redox flow of B. stearothermophilus protoplasts and induced significant perturbation of the structural order of bacterial lipid dispersions. We concluded that the bacterial model provides useful information about the nature and repercussion of membrane physical interactions of this lipophilic drug, on the basis of an easy and economic methodology.